Identification and therapeutic efficacy of Pleurotus djamor var fuscopruinosus - Monthien Phonemany; Phongeun Sysouphanthong; Narawadee Rujanapun; Satyajit D. Sarker; Lutfun Nahar; Panupong Puttarak; Poonsit Hiransai; Naritsada Thongklang; Rawiwan Charoensup (Scientific Reports)
Abstract Pleurotus is an edible mushroom that is consumed and cultivated worldwide. Pleurotus djamor var. fuscopruinosus is newly reported in Thailand, confirmed through morphological and phylogenetic analyses. Cultivation trials showed optimal mycelial growth on PDA, with sorghum supporting the highest spawn production. Sawdust was a suitable substrate, with fruiting bodies forming at 25–28 °C and 70–80% humidity, maturing within 4–5 days. Nutritional analysis (per 100 g dry weight) revealed 25.00 ± 1.5% protein, 15.99 ± 0.2% carbohydrates, 19.10 ± 0.9% fiber, 7.59 ± 1.0% ash, 2.07 ± 0.5% fat, and 30.25 ± 0.5% moisture. The 50% ethyl acetate extract exhibited the strongest antioxidant activity (IC50: 694.47 ± 3.92 µg/mL for DPPH; 652.92 ± 2.53 µg/mL for ABTS). The extract showed selective cytotoxicity against lung (A549, IC50 = 245.73 ± 7.60 µg/mL) and colorectal (SW480, IC50 = 382.03 ± 4.55 µg/mL) cancer cells but was less potent than doxorubicin (IC50 = 14.96 ± 1.58 µg/mL). Moderate cytotoxicity was observed in RAW 264.7 macrophages (IC50 = 213.08 ± 4.08 µg/mL). Antidiabetic potential was demonstrated through α-glucosidase inhibition, with the hot water extract (IC50 = 582.91 ± 3.0 µg/mL) showing the highest activity, followed by ethyl acetate (IC50 = 473.87 ± 1.4 µg/mL) and methanol (IC50 = 357.63 ± 3.3 µg/mL), comparable to acarbose (IC50 = 635.70 ± 4.9 µg/mL). Glucose consumption in 3T3-L1 adipocytes was enhanced (IC50 = 582.91 ± 3.0 µg/mL) but lower than metformin (IC50 = 99.58 ± 0.59 µg/mL). These results highlight P. djamor var. fuscopruinosus as a promising functional food with strong antioxidant, anticancer effects, and antidiabetic properties. Further studies should optimize cultivation, isolate bioactive compounds, assess safety, and validate therapeutic properties through in vivo studies.